THE CONCEPT OF DISCOURSE IN MODERN LINGUISTICS (ResearchJet Journal of Analysis and Inventions, 2021)
The article is devoted to the definition of the concept of discourse in linguistics through the prism of different approaches with the identification of the characteristics of each. Four approaches were chosen to consider the concept of discourse: communicative, structural-syntactic, structural-stylistic and socio-pragmatic. As a result of studying these approaches, it is revealed that one side of the discourse is addressed to pragmatics, to typical communication situations, the other - to the processes occurring in the minds of the participants of communication, and the third – to the text itself. This gave reason to believe that discourse can be considered both as a process and as a result in the form of a fixed text.